2015
DOI: 10.7574/cjicl.04.01.137
|View full text |Cite
|
Sign up to set email alerts
|

Planned Relocations in the Context of ClimateChange: Unpacking the Legal and Conceptual Issues

Abstract: Over the past six or so years, a wealth of research has sought to analyse conceptually, and document empirically, the links between climate change and human migration and displacement. However, considerably less attention has been given to planned relocations made necessary by the effects of climate change. This article seeks to contribute to the emerging policy debates over relocation as a form of adaptation to climate change. It begins by examining conceptual issues related to 'relocation' in light of existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 5 publications
0
40
0
1
Order By: Relevance
“…The Draft Articles are underpinned by general principles of international law, including respect for human dignity, human rights, nondiscrimination, and principles of humanity (McAdam and Ferris 2015). As the UN body of legal experts elected by states to promote the progressive development of international law and its codification, the ILC's Draft Articles, while not formally binding, carry considerable authority.…”
Section: Planned Relocation and State Responsibilitymentioning
confidence: 99%
“…The Draft Articles are underpinned by general principles of international law, including respect for human dignity, human rights, nondiscrimination, and principles of humanity (McAdam and Ferris 2015). As the UN body of legal experts elected by states to promote the progressive development of international law and its codification, the ILC's Draft Articles, while not formally binding, carry considerable authority.…”
Section: Planned Relocation and State Responsibilitymentioning
confidence: 99%
“…The UNFCCC's Taskforce on Displacement is currently developing recommendations to avert, minimise and address climate-related displacement, which includes planned relocation (Warsaw International Mechanism Executive Committee, 2017). Elsewhere it has been suggested that international adaptation funding mechanisms be used to fund resettlement schemes (McAdam and Ferris, 2015). Elsewhere it has been suggested that international adaptation funding mechanisms be used to fund resettlement schemes (McAdam and Ferris, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report by the Brookings Institution and UNHCR suggests that planned relocation will be needed once communities have passed a 'risk threshold' beyond which it is no longer safe for people to remain in place, and that relocation is less expensive than assisting people to rebuild their lives post-disaster (Brookings and UNHCR, 2015). Elsewhere it has been suggested that international adaptation funding mechanisms be used to fund resettlement schemes (McAdam and Ferris, 2015). These discussions and other publications (for instance de Sherbinin et al, 2011) have begun to position resettlement as a logical adaptive response to the impacts of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…However, amongst the literature and case studies in this growing field of research, 'less attention has been given to planned relocations made necessary by the effects of climate change ' (McAdam and Ferris 2015: 137). Moreover, there is no clear consensus about whether planned relocation (termed here as resettlement) in anticipation of, or as a response to, climate change impacts can be considered adaptation (Barnett and O'Neill 2011;McAdam and Ferris 2015). Adaptation measures should decrease a population's vulnerability to harm and exposure to environmental or other risks (Smit and Wandel 2006;Miller and Bowen 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After years of intransigence, a number of major international agreements across the areas of disasters, climate change, and sustainable development, that bring together national governments, the United Nations (UN) and other international actors and civil society, are beginning to concretely address the concerns associated with people who may have to move because of environmental changes. Despite this positive turn, much of this effort has focused on the issue of migration due to climate and other environmental changes, with planned resettlement in response to climate change (whether within or across international borders) remaining a poorly acknowledged and addressed area (de Sherbinin et al 2011;McAdam and Ferris 2015).…”
Section: Introductionmentioning
confidence: 99%